Siam Avoids Colonization, Bangkok is the Exchange - คุ้มสุภา, มาลินี (วารสารสหวิทยาการ, 2020)
Siam has never been a colony of Europe during the period of colonization, 1800s-1900s. To avoid British colonization, the Bangkok capital city subsequently privileged and welcomed British settlement in exchange for sovereignty. This article aims to answer the questions why Bangkok had done what it did. Who were the British subjects and what territories did the British settlements gain in Bangkok. After Siam and Britain negotiated for long duration, the conclusion of the final treaty, the Bowring Treaty came into force. In exchange, Siam had to privilege extraterritoriality rights and assign territories for the settlement of British and British subjects in Bangkok indefinitely. Regarding the treaty ratification in 1856, the definition of the British subject was clearly defined for care and protection. These people were natural born British or naturalized British subjects which included Asian colonizers known as “Asiatic subjects.” They were identified with certificates and passports. Consequently, the beneficial advantages of the treaty really attracted many immigrants coming to Bangkok in particular for the protection of rights and for the issuing of land owners with title deeds. Soon later, when new comers settled, they initially asked for road construction for trade in Bangkok for supporting commerce within British port networks. At the same time, British and British subjects’ communities settled naturally. Later Chinese and Indian communities densely settled in the south. From sojourner to settler, as a result of the treaty, British subjects finally became the settlers and citizens of Siam. So, it could be said that Siam avoided becoming a British colony, but in exchange she traded specific privileged rights, permitted the settlement of British and its subjects in Bangkok.